CDH11 inhibits proliferation and invasion in head and neck cancer. (10th July 2016) - Piao, Songlin; Inglehart, Ronald C.; Scanlon, Christina Springstead; Russo, Nickole; Banerjee, Rajat; D'Silva, Nisha J.
Abstract : Background: In this study, we use a bioinformatics‐based strategy to nominate a tumor suppressor gene cadherin‐11 (CDH11) and investigate its role in growth and invasion in head and neck squamous cell carcinoma (HNSCC). Methods: Using the Oncomine ™ database to compare HNSCC and normal specimens, CDH11 was nominated as having a role in HNSCC. CDH11 expression in HNSCC was evaluated by immunohistochemistry on a tissue microarray (TMA) and immunoblotting and immunofluorescence of cell lines. The functional impact of CDH11 on proliferation and invasion was evaluated after siRNA‐mediated knockdown. Results: In silico analysis suggested that CDH11 is overexpressed in HNSCC compared to normal specimens. HNSCC TMA exhibited a small but significant increase in intensity and proportion of CDH11. By immunoblot analysis, CDH11 was higher in 4/7 HNSCC cell lines compared to normal keratinocytes; CDH11 was highly upregulated in UM‐SCC‐47 and UM‐SCC‐74A and detectable in UM‐SCC‐14A and UM‐SCC‐29 cell lines. Downregulation of CDH11 in both UM‐SCC‐29 and UM‐SCC‐47 using two different siRNAs enhanced proliferation and invasion. Conclusion: CDH11 inhibits cell proliferation and invasion of HNSCC. This suggests that CDH11 functions as a tumor suppressor gene in head and neck cancer. Our findings emphasize the importance of verifying in silico findings with functional studies.